2017
DOI: 10.1177/2050312117696436
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tamsulosin and Tolterodine on double J stent–related symptoms: A double-blind, randomized, placebo-controlled trial

Abstract: Background:Ureteral double J stent are routinely applied for urologic patients although stent-related symptoms are common. Several attempts have been reported to minimize these symptoms.Objective:To compare Tolterodine, Tamsulosin, and placebo effects on double J stent–related symptoms.Material and method:In all, 125 patients (82 males and 43 females) with double J stent were randomly divided into three groups (group 1, n: 42, group2, n: 40 and group 3, n: 43). Each patient randomly received one pack of drug i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Numerous drugs had been tried to relieve these symptoms like alpha blockers, anticholinergics, phosphodiesterase inhibitors (PDE5Is) and analgesics. [6,7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] Silodosin is a highly selective alpha-1 adrenergic receptor antagonist which is used in the treatment of lower urinary tract symptoms (LUTS). Alpha-1 adrenergic receptors are densely found in the smooth muscle cells of the lower urinary tract, and silodosin relaxes them and improves the SRS, and various studies had also shown similar effect.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous drugs had been tried to relieve these symptoms like alpha blockers, anticholinergics, phosphodiesterase inhibitors (PDE5Is) and analgesics. [6,7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] Silodosin is a highly selective alpha-1 adrenergic receptor antagonist which is used in the treatment of lower urinary tract symptoms (LUTS). Alpha-1 adrenergic receptors are densely found in the smooth muscle cells of the lower urinary tract, and silodosin relaxes them and improves the SRS, and various studies had also shown similar effect.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] Anticholinergics can also improve SRS by reducing the involuntary bladder contraction that occurs due to trigone irritation. [18][19][20][21][22][23][24][25] PDE5Is increase levels of cGMP that will lead to relaxation of the smooth muscle of ureter and reduces SRS. [6,26] The aim of our study was to evaluate the efficacy and safety of silodosin, solifenacin, tadalafil, and their combinations in reducing DJ stent-related LUTS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the bladder mucosa normalised after the instillation. Table 4 provides a summary of existing studies about this issue, and most of the studies used the USSQ to measure the clinical discomfort caused by ureteric stenting [31][32][33][34][35][36][37][38][39][40][41]. As shown in Table 3, current existing evidence supports the specific treatment strategy to control discomfort due to ureteric stent indwelling either by a-blockers or other treatments.…”
Section: Discussionmentioning
confidence: 99%